(untitled) (AWKA JOURNAL OF ENGLISH LANGUAGE AND LITERARY STUDIES, 2024)
This paper explicates the commendable ideological actions and attitudes of Chinua Achebe as portrayed in Ezenwa-Ohaeto’s biography of the world-class writer and the inspirational effects of these actions and attitudes, with a view to presenting the biographee’s life as a significant source of inspiration to the readers. It is based on the descriptive and content analysis forms of qualitative research method, and Lesley Jeffries’ critical stylistic theory. Using the theoretical framework, seven classes of ideological structures are unveiled. These include: naming and descriptive structures, ideological structures involving actions, events and states, equating and contrasting ideological structures, implying and assuming structures, ideological structures with positive negations, presentation of others’ speech, and representing time, space and society. Crucially, the worth-adopting laudable ideologies communicated by the text producer are discovered as: commitment to true Christian practice, academic excellence, professional competence, good behaviour, honesty, humility, simplicity, hard work, reliability, selfless service to humanity, equal treatment for all, good interpersonal relationship, commitment to a good dream, fight against injustice, and purposeful existence. The paper thus encourages its readers to imbibe these laudable ideologies if they wish to live an impactful and outstanding life like the biographee. Keywords: , , , ,